Predictive Factors of Language Development in Persian-speaking Children Using Cochlear Implants: A Pilot Study - Mohammad Majid Oryadi-Zanjani; Tahereh Mohammadi; Zahra Mohammadi; Maryam Vahab (Journal of Rehabilitation Sciences and Research, 2021)
Background: This study aimed to investigate some child- and environmentdependentfactors in a retrospective method to find a prediction model for thespoken language development of children with hearing loss (HL) after cochlearimplantation (CI).Methods: The research reported here was conducted as a cross-sectional pilotstudy. The sample size was 18 Persian 5-to-7-year-old children with HL usingCI (6 girls and 12 boys) who were recruited via consecutive sampling methodsfrom Soroush Rehabilitation Center in Shiraz, Iran. The studied independentvariables were categorized into child-related variables and parental variables.At the first step, the participants were divided into two groups, good languageability, and poor language ability, based on the results of Sentence RepetitionTest (SRT). The correlation between the independent variables and SRT scores ofthe groups were compared in two stages.Results: Regarding the development of spoken language in two groups ofPersian-speaking preschool children using the cochlear implants with good andpoor language development, IQ, duration of watching TV, duration of playingwith the father, education status of the mother, education status of father,and economic status of the family had a significant correlation with languagedevelopment of these children.Conclusion: According to this study’s findings, the child’s IQ, the duration ofwatching TV during the day, the duration of playing with the father during theday, the level of education of the mother, the level of education of the father, andthe economic level of the family may be considered the predictive factors in thelanguage development of cochlear implant children during the preschool years.